Apigenin Decreases Acinar Cell Damage in Pancreatitis. Issue 5 (May 2019) - Mrazek, Amy A.; Bhatia, Vandanajay; Falzon, Miriam; Spratt, Heidi; Chao, Celia; Hellmich, Mark R.
Abstract : Objective: Chronic pancreatitis is the consequence of multiple episodes of recurrent acute pancreatitis (RAP). We hypothesized that apigenin can minimize the sequelae of RAP by limiting acinar cells' proinflammatory signaling pathways. Methods: AR42J acinar cells were treated in vitro with transforming growth factor β (TGF-β), apigenin, and other inhibitors. Dual luciferase reporter assay measured parathyroid hormone–related protein (PTHrP) promoter activity. MAPK/ERK pathway activity was assessed by immunoblotting and in vivo by immunohistochemistry with a cerulein-induced RAP mouse model. Nuclear factor κ B nuclear localization was analyzed in vitro in cells stimulated with tumor necrosis factor α. Primary acini were isolated and treated with cerulein; interleukin 6 messenger RNA was measured comparing PTHrP wild-type and knockout mice. Results: Apigenin and PD98059 each downregulated TGF-β stimulation of PTHrP P3 promoter activity. In a RAP mouse model, apigenin reduced pERK nuclear localization in acinar cells and preserved acinar cell architecture. Apigenin suppressed tumor necrosis factor α–mediated signaling by decreasing nuclear factor κ B nuclear localization and decreased interleukin 6 messenger RNA levels via a PTHrP-dependent mechanism. Conclusions: Apigenin reduced inflammatory responses in experimental models of RAP. The mechanisms mediating the actions of apigenin, in part, are owing to attenuation of PTHrP and TGF-β proinflammatory signaling.